The endocrinology of the urinary bladder - Saptarshi Bhattacharya; Arbinder Kumar Singal; Sanjay Kalra (Journal of the Pakistan Medical Association, 2023)
The urinary bladder primarily functions as a reservoir for urine. Apparently, it serves only a mechanical and passive role in the urinary tract, but closer scrutiny reveals that it has several meaningful endocrine interactions. This vital organ has an intricate plexus of neurons that release neurohormones concerned with the functioning of the bladder. Endocrine disorders, most notably diabetes, can cause a broad spectrum of bladder dysfunction. The current review explores the bladder as a source of neurotransmitters, a target for organ damage due to uncontrolled endocrinopathy, a beneficiary of hormonal therapy, and a tool to improve endocrine health. Keywords: Urinary bladder, diabetes, lower urinary tract symptoms, overactive bladder, urinary obstruction